2016
DOI: 10.1108/scm-05-2016-0143
|View full text |Cite
|
Sign up to set email alerts
|

The role of motivation in relating green supply chain management to performance

Abstract: Purpose Not all companies deal with green supply chain management (GSCM) in the same way. The purpose of this paper is to understand a company’s GSCM motivation and how this motivation is linked to stakeholder pressures, a company’s GSCM practices and performance. Design/methodology/approach The authors report the findings of a survey on GSCM motivations. Findings Clear differences are seen in why companies are motivated to pursue GSCM. Based on these different motivations, this paper explains differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 62 publications
(89 reference statements)
2
26
0
Order By: Relevance
“…This finding is similar to that of Graves, Sarkis, and Zhu (). Motivation in the context of GCSM mediates the relationship between stakeholder pressures and performances (Nie, Zhu, & Jin, ; Vanpoucke, Quintens, & Van Engelshoven, ). From the supported hypotheses (Table ), we conclude that green motivation enhances safety in the workplace, empowerment, and reducing health hazards in the Indian mining industry. Teamwork has been found to be crucial for effective GCSM implementation in the Indian mining sector. This is well supported by Daily et al (); this study revealed that teams who are conscious about environmental issues work in an environmentally responsible way that leads to enhanced GCSM performance. Green innovation, another important behavioural factor included in our study, is seen to have significant influence on GCSM performance.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to that of Graves, Sarkis, and Zhu (). Motivation in the context of GCSM mediates the relationship between stakeholder pressures and performances (Nie, Zhu, & Jin, ; Vanpoucke, Quintens, & Van Engelshoven, ). From the supported hypotheses (Table ), we conclude that green motivation enhances safety in the workplace, empowerment, and reducing health hazards in the Indian mining industry. Teamwork has been found to be crucial for effective GCSM implementation in the Indian mining sector. This is well supported by Daily et al (); this study revealed that teams who are conscious about environmental issues work in an environmentally responsible way that leads to enhanced GCSM performance. Green innovation, another important behavioural factor included in our study, is seen to have significant influence on GCSM performance.…”
Section: Discussionmentioning
confidence: 99%
“…This study examines the impact of corporate motives on SSCM practices and the TBL performance. Extant research argued that firms can be motivated in different ways and that SC sustainability outcomes are determined by their varying motivation (Vanpoucke et al, 2016). Indeed, corporate motives is one of the crucial drivers of SSCM initiatives and was a subject of several studies (Wolf, 2014;Paulraj et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Facing growing pressures on multiple fronts, corporations may opt to accelerate their sustainability actions, as addressing stakeholders pressures is vital in increasing corporate legitimacy and achieving corporate objectives (Hofmann et al, 2014;Lo and Shiah, 2016). Although firms driven by legitimization aim to meet, rather than exceed, regulations and norms (Vanpoucke et al, 2016), legitimacya relational motiveis invaluable in fostering good relationships and reinforcing good will. Indeed, neglecting stakeholders' demands may damage corporate reputation.…”
Section: Relational Motives and Sustainable Supply Chain Management Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…While numerous researchers have touted stakeholder pressures as the predominant driver of SSCM implementation (e.g. Morali and Searcy, 2013; Zhu et al , 2013; Wolf, 2014), others argue that the key driver is not simply the pressure of various stakeholders (Vanpoucke et al , 2016). Specifically, scholars in business ethics and organizational justice advocate that morality-based motives play a critical role in the actions taken by supply chain organizations (Carroll, 1991; Cropanzano et al , 2003; Aguilera et al , 2007).…”
Section: Sscm Antecedentsmentioning
confidence: 99%